The effect of psychological capital on conflicts in the work-family interface, turnover and absence intentions - Karatepe, Osman M.; Karadas, Georgiana (Elsevier Sci Ltd, 2014)
Using Conservation of Resources (COR) and congruence theories as the theoretical underpinnings, the present study develops and tests a research model that investigates the impact of psychological capital (PsyCap) on work-family conflict, family-work conflict, and turnover and absence intentions. The model also examines the effects of two directions of conflict on these employee outcomes. Self-efficacy, hope, optimism, and resilience are the components representing PsyCap. Based on data obtained from frontline hotel employees with a time lag of two weeks in three waves in Romania, the results suggest that Psycap mitigates work-family conflict, family-work conflict, and turnover and absence intentions. The results further suggest that PsyCap influences the aforesaid employee outcomes indirectly through family-work conflict. However, work-family conflict has no bearing on these outcomes. Theoretical and practical implications are discussed in the study. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Absence intentions; Family-work conflict; Hotel employees; Psychological capital; Romania; Turnover intentions; Work-family conflict